Evaluasi Pemanfaatan Aplikasi Game dalam Ujian Bahasa Indonesia (Studi Kasus di SMAN 1 Polanharjo Klaten) - Yanuar Bagas Arwansyah; Nina Queena Hadi Putri; Ryan Hidayat; Khusnul Khotimah; Sarwiji Suwandi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to evaluate the implementation of the exam by utilizing game applications in Indonesian subjects at SMA Negeri 1 Polanharjo. This study involved a teacher and four students, consisting of two students in class X and two in class XI. This research uses a qualitative approach with a case study strategy; research data is obtained by observation and interviews; data validity is done by triangulation of data and sources. The results of the research: (1) the implementation of the Indonesian language exam at SMA Negeri 1 Polanharjo has used the Scorative game application as a learning evaluation tool; (2) the advantages of using Scorative games in exams, namely making students more enthusiastic in carrying out exams and making the exam atmosphere more fun; (3) deficiencies in the use of Scorative games, namely that they cannot be used for large-scale examinations due to limited facilities and infrastructure as well as the competence of human resources in the use of technology; and (4) obstacles that arise in the implementation of game-based exams, namely the readiness factor for the quality and quantity of devices, networks, and the level of students' understanding of the use of applications.